OUR EXPERIENCE WITH 3D CT - Pach, Miroslav; Ditmar, Rudolf; Herman, Miroslav (Biomedical papers, 1999)
The authors present the results of 9-year work with 3D CT in orthopaedics and musculoskeletal traumatology.In the years 1990-1998, the method was used in the examination of 59 patients (27 males, 20 females, and 12children). The place of 3D CT in clarifying areas of complex musculoskeletal anatomy for operative treatment isdiscussed and presented as a contribution to the indication conference. According to the authors' experience, inmany cases 3D CT increases the quality of diagnostics. Most of all, it helps the surgeon in operation planning. 3Dreconstructions are particularly valuable in proximal humerus fractures, spine fractures and tumours, acetabulumfractures, as well as in conditions after hip dysplasia, LCPD and coxa vara adolescent.
Keywords: Three-dimensional CT/ Orthopaedic diseases/ Musculoskeletal traumas